RibDif: can individual species be differentiated by 16S sequencing? - Strube, Mikael Lenz (Bioinformatics Advances, 2021)
Motivation Metataxonomic analysis is now routinely used to profile the microbiome of virtually every ecological niche on planet Earth. The use of amplicon sequence variants (ASVs), proposing to be the exact biological 16S rRNA amplicon sequences of a given biological system, is now considered the gold standard. However, the 16S rRNA genes, and in particular the amplicons derived from it, are not unique for most species nor are they necessarily unique within individual genomes. Despite these restrictions, individual ASVs are often used to make inferences on the state of a given ecosystem, which may cause erroneous conclusions on the effects of a given species on a specific host phenotype or ecosystem. Results: To support researchers working with metataxonomics, we have developed RibDif, which easily and rapidly evaluates the feasibility of using metataxonomics to profile individual species. We use RibDif to demonstrate that the genus Pseudoalteromonas contains species that are impossible to distinguish with 16S amplicons and that this is a common motif in bacterial genera. We propose that researchers consult RibDif when making conclusions on individual species from metataxonomic data. Availability and implementation RibDif is freely available along with source code and detailed documentation at https://github.com/mikaells/RibDif.